The Effect of Fibrosis on DNA Yield from Formalin Fixed Paraffin Embedded Tissues - Naveed, Muhammad; Tariq, Hassan; Gul, Asma; Arzo, Natasha; Hussain, Muhammad; Buksh, Sumaira (Pakistan Armed Forces Medical Journal, 2024)
Objective: To report the effect of fibrosis on yield of Deoxyribonucleic Acid extraction from Formalin-Fixed Paraffin-Embedded tissue. Study Design: Cross sectional study. Place and Duration of Study: Department of Molecular Pathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, Jul to Dec 2021. Methodology: Fifty-four Formalin-Fixed Paraffin-Embedded tissues having size <2cm containing fibrosis (Mild, Moderate, Severe) were included in the study. Formalin-Fixed Paraffin-Embedded tissues having tissue size > 2cm were excluded. Deoxyribonucleic Acid was extracted and quantified from Formalin-Fixed Paraffin-Embedded blocks. Results: Nine (17%) Formalin-Fixed Paraffin-Embedded tissues had no fibrosis, 28(51%) had Mild fibrosis, 9(17%) and 8(15%) had Moderate and Severe fibrosis. Measurement scale in 5 different stages for evaluation of our quantified results were used. For specimens with no fibrosis the DNA quantity fell on scale 1, 0(0%); on scale 2, 1(11%); on scale 3, 0(0%); on scale 4, 1(11%); and on scale 5, 7(78%). Deoxyribonucleic Acid yield in moderate fibrosis specimens fell on scale 1, 0(0%)’ on scale 2, 7(78%); on scale 3, 0(0%); on scale 4, 1(11%); and on scale 5, 1(11%). Among severe fibrosis the Deoxyribonucleic Acid quantity fall on scale 1, 5(62%); on scale 2, 3(38%); on scale 3, 0(0%); on scale 4, 0(0%); and on scale 5, 0(0%). Conclusion: Formalin-Fixed Paraffin-Embedded tissues having severe fibrosis resulted in significantly lower Deoxyribonucleic Acid yield as compared to Formalin-Fixed Paraffin-Embedded tissues having no fibrosis